2012
DOI: 10.1016/j.jmb.2011.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Coiled-Coil Tip of Escherichia coli DksA in Promoter Control

Abstract: E. coli DksA works in conjunction with the small molecule ppGpp to regulate transcription initiation negatively or positively, depending on the identity of the promoter. DksA is in a class of transcription factors that do not bind directly to DNA like classical repressors or activators but rather bind in the RNA polymerase (RNAP) secondary channel like the transcription elongation factors GreA and GreB in E. coli and TFIIS in eukaryotes. We found that substitution for either of two residues in its coiled-coil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
69
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(79 citation statements)
references
References 36 publications
9
69
1
Order By: Relevance
“…This assignment is supported by cross-linking between DksA-V73 and the overlapping region (β653-681) as well as functional analysis of mutants in D74, β-R678, and β-R1106. We found that DksA-D74 substitutions D74N, D74S, and D74E all altered DksA activity without affecting binding, consistent with previous studies (3,12,21) (Fig. 5B and SI Appendix, Fig.…”
Section: Significancesupporting
confidence: 91%
See 2 more Smart Citations
“…This assignment is supported by cross-linking between DksA-V73 and the overlapping region (β653-681) as well as functional analysis of mutants in D74, β-R678, and β-R1106. We found that DksA-D74 substitutions D74N, D74S, and D74E all altered DksA activity without affecting binding, consistent with previous studies (3,12,21) (Fig. 5B and SI Appendix, Fig.…”
Section: Significancesupporting
confidence: 91%
“…Our experimental efforts focused on the effects of DksA during initiation, but the position of the DksA coiled-coil in the channel may be dynamic and vary with RNAP conformation, the stage of transcription cycle, and the presence of additional factors such as ppGpp. Indeed, Fe 2+ -mediated cleavage of DksA is reduced for nonfunctional DksA-tip mutants (21), and in the paused complex as compared to free RNAP (20). This reduced cleavage has been interpreted as representing a more distal position of the coiled-coil in the these complexes (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The active residue of DksA (aspartic acid 74) is located at the tip of the coiled-coil domain, which would contact the trigger loop (TL) of RNAP. Such an interaction was recently tested using various DksA-GreA/B chimeras where the Gre factors could mimic DksA and initiate transcription when equipped with a DksA-like active tip (37). Additionally, DksA acts antagonistically to GreA in the regulation of rRNA promoters, which suggests that both molecules compete for the same surface on RNAP (38)(39)(40)(41).…”
mentioning
confidence: 99%
“…DksA exerts its effects by binding directly to the secondary channel of RNAP and allosterically modifying the kinetic properties of the enzyme, thereby sensitizing RNAP to changes in the concentrations of guanosine tetraphosphate (ppGpp) and the initiating nucleoside triphosphate (iNTP) (26,29,34,35). D74, an aspartate residue at the tip of the coiled-coil domain, is necessary for DksA to function in transcription initiation (16). In addition, DksA aids in resolving conflicts between the active DNA replication machinery and stalled or elongating RNA polymerases, and it helps to ensure the proper resolution of double-strand breaks caused by these collisions (22,42,45).…”
mentioning
confidence: 99%